Polski sektor spółdzielczy w latach 2001–2011 - Wyrzykowska, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
This paper assesses the position of the cooperative sector in Polish national economy in the years 2001–2011. The study is based mainly on publicly available information such as scientific publications and databases of the Central Statistical Office (GUS) and the National Council for Cooperative. The article used comparative analysis. The analysis showed that in recent years the share of the cooperative sector in the national economy declined. The number of cooperatives has steadily decreased, having different causes and effects depending on the industry. Financial and economic crisis has shown that cooperative banking plays an important role in the stabilization of the financial market.